Catalyst Protonation Changes the Mechanism of Electrochemical Hydride Transfer to CO2 - Lee, Kevin YC; Polyansky, Dmitry E; Grills, David C; Fettinger, James C; Aceves, Marcos; Berben, Louise A (ACS Organic & Inorganic Au, 2024)
It is well-known that addition of a cationic functional group to a molecule lowers the necessary applied potential for an electron transfer (ET) event. This report studies the effect of a proton (a cation) on the mechanism of electrochemically driven hydride transfer (HT) catalysis. Protonated, air-stable [HFe4N(triethyl phosphine (PEt3))4(CO)8] (H4) was synthesized by reaction of PEt3 with [Fe4N(CO)12]- (A -) in tetrahydrofuran, with addition of benzoic acid to the reaction mixture. The reduction potential of H4 is -1.70 V vs SCE which is 350 mV anodic of the reduction potential for 4 -. Reactivity studies are consistent with HT to CO2 or to H+ (carbonic acid), as the chemical event following ET, when the electrocatalysis is performed under 1 atm of CO2 or N2, respectively. Taken together, the chemical and electrochemical studies of mechanism suggest an ECEC mechanism for the reduction of CO2 to formate or H+ to H2, promoted by H4. This stands in contrast to an ET, two chemical steps, followed by an ET (ECCE) mechanism that is promoted by the less electron rich catalyst A -, since A - must be reduced to A 2- before HA - can be accessed.